Green awareness through environmental knowledge and perceived quality - Alamsyah, Doni Purnama; Othman, Norfaridatul Akmaliah; Bakri, Mohammed Hariri; Yogi Udjaja; Rudy Aryanto (Growing Science, 2020)
Green awareness is worth researching to determine the customer consumption pattern of environment-friendly products. Several research models are showing the importance of green awareness of customer behavior. This paper studies the role of information in marketing decisions related to customer green awareness. Based on the phenomenon of green awareness, this research work aims to study the role of customer green awareness built through eco-label, environmental knowledge, and perceived quality. This experimental research is conducted on 200 supermarket customers who had experience with green products. The data is collected through a questionnaire and analyzed using the Structural Equation Model approach. SmartPLS is conducted to test the research hypotheses. The findings show that there was a relationship between the eco-label credibility of environment-friendly products on the customers' increased environmental knowledge and perceived quality of the products. Besides, both environmental knowledge and perceived quality are identified to play an essential role in controlling green awareness. Eco-label in product attributes is found to be capable of changing the positive side of green awareness. These findings describe a model in developing green awareness through environmental knowledge and perceived quality with the support of environment-friendly product eco-label. The model also can predict customer green awareness and support the green marketing strategy. Therefore, further research works on green customer behavior are welcome, as green customer behavior must impact on the implementation of green marketing strategies. Also, we may predict the customer behavior of environment-friendly products, and implement better business strategies